Operationalising children’s rights principles: an indicator framework for policy analysis - Aida Kišūnaitė; Ly Hai Bui (Revista Sobre la Infancia y la Adolescencia)
Despite decades-old political commitments to mainstreaming children’s rights in policy initiatives, there remains inadequacy of children’s rights-based monitoring and evaluation instruments for this progress. As an effort to address this gap, the paper seeks to conceptualise the children’s rights-based approach and to propose its application to policy analysis. Recognising children as rights holders and the state as the primary duty bearer, the core of the children’s rights-based approach is at ensuring the enjoyment and realisation of children’s rights through a number of principles. This paper’s proposed assessment framework focuses on the state’s legal structure, policy measures, and outcomes achieved in the realisation and enjoyment of children’s rights and the evaluation of policy progress under child rights norms and principles. Accordingly, the children’s rights-based policy analysis is designed to be based on two sets of indicators that reflect the state’s policy commitment and child rights principles.